2016
DOI: 10.1007/s11743-016-1815-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Softening Mechanism in Rinse‐Cycle Fabric Softeners. Part 2: Uneven Adsorption—The Key Phenomenon to the Effect of Fabric Softeners

Abstract: We investigated the actual factor determining the softening effect of a fabric softener. The adsorption area of the softener on model cotton cloths and yarns was identified using bromophenol blue. There was almost no softener at the cross-points of the yarns in the cloth samples or in the inner part of the yarns. The softening performance was better when there was less softener at the cross-points of the yarns than when the yarns were evenly covered by the softener. Thus we conclude that the presence of soften… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 8 publications
1
29
1
Order By: Relevance
“…Recent studies have correlated fabric frictional characteristics with smoothness and softness [10], while others have put forward that the friction between the human skin and fabrics has a more prominent role [11]. Following Igarashi et al the softening effect would come from the reduction of H-bonding between the bound water molecules and the cotton fibers [12,13]. Crutzen has suggested that hydrophobic interactions derived from the long alkyl chains of cationic surfactants are the primary driving force for adsorption [14], whereas Kumar et al proposed that the deposition process is electrostatically driven and that intact vesicles adsorb on cotton or viscose fibers [5,15].…”
mentioning
confidence: 99%
“…Recent studies have correlated fabric frictional characteristics with smoothness and softness [10], while others have put forward that the friction between the human skin and fabrics has a more prominent role [11]. Following Igarashi et al the softening effect would come from the reduction of H-bonding between the bound water molecules and the cotton fibers [12,13]. Crutzen has suggested that hydrophobic interactions derived from the long alkyl chains of cationic surfactants are the primary driving force for adsorption [14], whereas Kumar et al proposed that the deposition process is electrostatically driven and that intact vesicles adsorb on cotton or viscose fibers [5,15].…”
mentioning
confidence: 99%
“…Since the fiber rigidity, and therefore its processability, is related to the cellulose crystallinity, the reduction of the crystalline portion, with consequent increase of the amorphous region, implies an increase of the fiber softness. A reduction of the fiber crystallinity can be obtained through the use of a softener, since, according to Igarashi et al, the softening effect of a fabric softener could be ascribed to the loss of some hydrogen bonds and Van der Waals interactions between the ordered polymeric chains, probably due to the “insertion” of softeners micelles 21 , 22 . On this basis, the measurement of the Crystallinity Index (CI) could represent an important parameter for assessing the fiber workability (fiber strength and elasticity).…”
Section: Resultsmentioning
confidence: 99%
“…One is that the softener molecules reduce the friction between adjacent fibers because they form a structured hydrophobic layer on the cellulose surface by exposing their alkyl tails toward the air after the drying process 21 . The other one is that the softeners prevent the formation of cross-linking bound water layers between the fibers during the drying process, which otherwise increases the fiber stiffness 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a clear need to develop special softening agents for this kind of papers or debonding agents for uff pulp board. In order to make the nal tissue products possess high antibacterial activity and at the same time create enough softness or appropriate burst strength, antibacterial agents (Hayashi et al 2019;Xu et al 2020) and softening/debonding agent (Igarashi et al 2016) are usually added together during the papermaking process. However, there are few reports on chemical additives which have both antibacterial and softening/debonding effects.…”
Section: Introductionmentioning
confidence: 99%